In vitro and In vivo Antioxidant Effect of Mango, Coconut and Cotton Seed Oils on Hydrogen Peroxide- Induced Oxidative Stress in Wistar Rats - Ochida, Comfort Onyeche; Itodo , Adams Udoji; Anhwange, Benjamin Asen; Onoja, Peter Onyeholowo; Nwanganga , Promise Adaku (Sahel Journal of Life Sciences FUDMA, 2024)
This study is aimed at determining the antioxidant activity of Mango kernel oil (MKO), Coconut oil (CCO) and Cotton seed oil (CSO) in vitro and in vivo. Antioxidant parameters demonstrated by five spectrophotometric methods such as: DPPH, FRAP, MCA, HRSA and SRSA was determined in the oils. Superoxide dismutase activity (SOD), catalase activity (CAT) and malondialdehyde (MDA) were evaluated in the serum of the Wistar rats. The antioxidant assay of the oils showed Coconut oil (75.67±0.21 %) was able to neutralize the DPPH radical more than the other oils followed by Cotton seed oil (38.70±0.23 %) and Mango kernel oil (31.56±0.24 %). Coconut oil exhibited the highest FRAP activity at (1.04 mMolFe2+) while the Cotton seed oil displayed significantly lower (P< 0.05) FRAP activity at (0.18±0.00 mMolFe2+). The Metal chelating activity (MCA) of Coconut oil (52.72±0.24 %) was found to be significantly higher than Mango and Cotton seed oils, Superoxide radical scavenging activity showed Coconut oil (62.36±0.01 %) having a relatively high ability to scavenge superoxide radicals better than the other oils with the standard glutathione being significantly higher (81.36±0.07 %). The result of the in vivo study showed the mean values for the SOD of MKO (118.10±5.39 IU/L), CCO (120.53±4.53 IU/L) and CSO (108.80±3.33 IU/L), CAT of MKO (108.93±11.60 IU/L), CCO (96.85±11.69 IU/L) and CSO (88.28±10.66 IU/L) and MDA of MKO (0.25±0.07 mmol/L), CCO (0.24±0.14 mmol/L) and CSO (0.31±0.02 mmol/L). The oils markedly reduced the amount of MDA while significantly increasing the activities of both CAT and SOD content.